Latest Advances in Endothelial Progenitor Cell-Derived Extracellular Vesicles Translation to the Clinic - Salybekov, Amankeldi A.; Kunikeyev, Aidyn D.; Kobayashi, Shuzo; Asahara, Takayuki (Frontiers in Cardiovascular Medicine, 2021)
Almost all nucleated cells secrete extracellular vesicles (EVs) that are heterogeneous spheroid patterned or round shape particles ranging from 30 to 200 nm in size. Recent preclinical and clinical studies have shown that endothelial progenitor cell-derived EVs (EPC-EVs) have a beneficial therapeutic effect in various diseases, including cardiovascular diseases and kidney, and lung disorders. Moreover, some animal studies have shown that EPC-EVs selectively accumulate at the injury site with a specific mechanism of binding along with angiogenic and restorative effects that are superior to those of their ancestors. This review article highlights current advances in the biogenesis, delivery route, and long-term storage methods of EPC-EVs and their favorable effects such as anti-inflammatory, angiogenic, and tissue protection in various diseases. Finally, we review the possibility of therapeutic application of EPC-EVs in the clinic.